Salivaricin G32, a Homolog of the Prototype Streptococcus pyogenes Nisin-Like Lantibiotic SA-FF22, Produced by the Commensal Species Streptococcus salivarius - Philip A. Wescombe; Kristin H. Dyet; Karen P. Dierksen; Daniel A. Power; Ralph W. Jack; Jeremy P. Burton; Megan A. Inglis; Anna L. Wescombe; John R. Tagg (International Journal of Microbiology)
Salivaricin G32, a 2667 Da novel member of the SA-FF22 cluster of lantibiotics, has been purified and characterized from Streptococcus salivarius strain G32. The inhibitory peptide differs from the Streptococcus pyogenes—produced SA-FF22 in the absence of lysine in position 2. The salivaricin G32 locus was widely distributed in BLIS-producing S. salivarius, with 6 (23%) of 26 strains PCR-positive for the structural gene, slnA. As for most other lantibiotics produced by S. salivarius, the salivaricin G32 locus can be megaplasmid encoded. Another member of the SA-FF22 family was detected in two Streptococcus dysgalactiae of bovine origin, an observation supportive of widespread distribution of this lantibiotic within the genus Streptococcus. Since the inhibitory spectrum of salivaricin G32 includes Streptococcus pyogenes, its production by S. salivarius, either as a member of the normal oral microflora or as a commercial probiotic, could serve to enhance protection of the human host against S. pyogenes infection.